The Key Enzymes in the Suberin Biosynthetic Pathway in Plants: An Update - Gal Nomberg; Ofir Marinov; Gulab Chand Arya; Ekaterina Manasherova; Hagai Cohen (Plants, 2022)
Suberin is a natural biopolymer found in a variety of specialized tissues, including seed coat integuments, root endodermis, tree bark, potato tuber skin and the russeted and reticulated skin of fruits. The suberin polymer consists of polyaliphatic and polyphenolic domains. The former is made of very long chain fatty acids, primary alcohols and a glycerol backbone, while the latter consists of p-hydroxycinnamic acid derivatives, which originate from the core phenylpropanoid pathway. In the current review, we survey the current knowledge on genes/enzymes associated with the suberin biosynthetic pathway in plants, reflecting the outcomes of considerable research efforts in the last two decades. We discuss the function of these genes/enzymes with respect to suberin aromatic and aliphatic monomer biosynthesis, suberin monomer transport, and suberin pathway regulation. We also delineate the consequences of the altered expression/accumulation of these genes/enzymes in transgenic plants.